Smoking and subsequent risk of leukemia in Japan: The Japan Public Health Center-based Prospective Study - Tomotaka Ugai (Journal of Epidemiology, 2017)
Background: Cigarette smoking has been reported to be associated with an increased risk of leukemia. Most epidemiological evidence on the association between cigarette smoking and leukemia risk is from studies conducted in Western populations, however, and evidence from Asian populations is scarce.